Serglycin-Deficiency Causes Reduced Weight Gain and Changed Intestinal Cytokine Responses in Mice Infected With Giardia intestinalis - Li, Zhiqiang; Peirasmaki, Dimitra; Svärd, Staffan; Åbrink, Magnus (Frontiers in Immunology, 2021)
The proteoglycan serglycin (SG) is expressed by different innate and adaptive immune cells, e.g. mast cells, macrophages, neutrophils and cytotoxic T lymphocytes, where SG contributes to correct granule storage and extracellular activity of inflammatory mediators. Here the serglycin-deficient (SG-/-) mouse strain was used to investigate the impact of SG on intestinal immune responses during infection with the non-invasive protozoan parasite Giardia intestinalis. Young (≈11 weeks old) oral gavage-infected congenic SG-/- mice showed reduced weight gain as compared with infected SG+/+,+/- littermate mice and the PBS-challenged SG-/- and SG+/+,+/- littermate mice. The infection caused no major morphological changes in the small intestine. However, a SG-independent increased goblet cell and granulocyte cell count was observed, which did not correlate with increased myeloperoxidase or neutrophil elastase activity. Furthermore, infected mice showed increased serum IL-6 levels, with significantly reduced serum IL-6 levels in infected SG-deficient mice and decreased intestinal expression levels of IL-6 in the infected SG-deficient mice. In infected mice the qPCR analysis of alarmins, chemokines, cytokines, and nitric oxide synthases (NOS), showed that the SG-deficiency caused reduced intestinal expression levels of TNF- and CXCL2, and increased IFN-, CXCL1 and NOS1 levels as compared with SG-competent mice. This study shows that SG plays a regulatory a role in intestinal immune responses, reflected by changes in chemokine and cytokine expression levels and a delayed weight gain in young SG-/- mice infected with G. intestinalis.